Age and periodic replacement policies with two failure modes in general replacement models. (October 2021) - Mizutani, Satoshi; Zhao, Xufeng; Nakagawa, Toshio
Abstract: This paper studies age and periodic replacement policies in general replacement models by considering major failures and minor failures, meanwhile, random replacement policies are applied as alternatives for regular policies into replacement first and last models. We obtain the expected cost rates for each planned replacement policies. Optimal regular replacement and random replacement policies are discussed and compared from the point of cost in analytical ways. Furthermore, exponential minor failure, exponential major failure, and Weibull major failure with an increasing hazard rate of minor failure are illustrated in numerical analyses. Highlights: Age and periodic replacement policies are modeled into general replacement models. Regular and random replacement policies are modeled into general replacement models. Replacement first and last policies are modeled for general replacement models. Replacement first and last policies are compared from the point of cost.